Effect of Saturated Stearic Acid on MAP Kinase and ER Stress Signaling Pathways during Apoptosis Induction in Human Pancreatic β-Cells Is Inhibited by Unsaturated Oleic Acid - Šrámek, Jan; Němcová-Fürstová, Vlasta; Pavlíková, Nela; Kovář, Jan (International journal of molecular sciences, 2017)
It has been shown that saturated fatty acids (FAs) have a detrimental effect on pancreatic β-cells function and survival, leading to apoptosis, whereas unsaturated FAs are well tolerated and are even capable of inhibiting the pro-apoptotic effect of saturated FAs. Molecular mechanisms of apoptosis induction and regulation by FAs in β-cells remain unclear; however, mitogen-activated protein (MAP) kinase and endoplasmic reticulum (ER) stress signaling pathways may be involved. In this study, we tested how unsaturated oleic acid (OA) affects the effect of saturated stearic acid (SA) on the p38 mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinase (ERK) pathways as well as the ER stress signaling pathways during apoptosis induction in the human pancreatic β-cells NES2Y. We demonstrated that OA is able to inhibit all effects of SA. OA alone has only minimal or no effects on tested signaling in NES2Y cells. The point of OA inhibitory intervention in SA-induced apoptotic signaling thus seems to be located upstream of the discussed signaling pathways.
Keywords: Humans; Stearic Acids; p38 mitogen-activated protein kinase (MAPK); extracellular signal-regulated kinase (ERK); lidé; p38 Mitogen-Activated Protein Kinases; apoptosis; apoptóza; mitogenem aktivované proteinkinasy p38; buněčné linie; kyselina olejová; Cell Line; endoplasmic reticulum (ER) stress; stres endoplazmatického retikula; Insulin-Secreting Cells; Endoplasmic Reticulum Stress; Oleic Acid; fatty acids; MAP Kinase Signaling System; kyseliny stearové; beta-buňky; NES2Y; pancreatic β-cells; Apoptosis; MAP kinasový signální systém